Answer: Choice B) x = 1
================================================
Step-by-step explanation:
The problem should read 6^(3-x) = 6^2. The 3-x must be in parenthesis to indicate that all of "3-x" is in the exponent and not just the 3.
Because both bases are 6, and because both sides are equal, this means that the exponents must be equal as well. Therefore 3-x = 2. Let's solve for x
3-x = 2
3-x+x = 2+x .... adding x to both sides
3 = 2+x
2+x = 3 ..... flipping both sides
x+2 = 3
x+2-2 = 3-2 .... subtracting 2 from both sides
x = 1
You can use logarithms to solve this problem, but the fact that the bases are both the same allows us to use this faster shortcut.